You reap what you sow: The role of Karma in Green purchase - Chairy Chairy; Jhanghiz Syahrivar (Cogent Business & Management, 2020)
In line with the growing popularity of the green economy in recent years, green marketing is also gaining more prominence in the academic world. One interesting research direction in this area is the role of religion in the consumption of green products. This is the first study that investigates the role of "Karma" in the green purchase intention of Buddhist minority in Indonesia-most of them are Chinese descent. Karma, a doctrine most prominent in Buddhism, is the belief that one's deeds in the present will influence his or her fate in the future or in the next life. In this study, spirituality and long-term orientation were predicted to mediate the relationship between karma and green purchase intention. For this study, we gathered 148 Indonesian Buddhists. We employed Composite Confirmatory Analysis via ADANCO PLS-SEM software to analyse the hypotheses and derive our conclusion. The results of this study reveal that 1) karma has a positive effect on green purchase intention, 2) There is a partial mediation of spirituality in the relationship between karma and green purchase intention and, 3) Karma has a positive effect on spirituality and long-term orientation. Theoretical contribution as well as managerial implications of this study, especially for green marketing practitioners targeting Buddhist consumers, are discussed.
Keywords: 650; karma; spirituality; long-term orientation; green purchase intention